Subjective sleep complaints indicate objective sleep problems in psychosomatic patients: a prospective polysomnographic study - Linden M (Dove Medical Press, 2016)
Michael Linden,1,2 Marie Dietz,1 Christian Veauthier,3 Ingo Fietze3 1Research Group Psychosomatic Rehabilitation, Charité University Medicine Berlin, 2Department of Psychosomatic Medicine, Rehabilitation Centre Seehof, Teltow, 3Interdisciplinary Center of Sleep Medicine, Charité University Medicine Berlin, Berlin, Germany Objective: To elucidate the relationship between subjective complaints and polysomnographical parameters in psychosomatic patients.Method: A convenience sample of patients from a psychosomatic inpatient unit were classified according to the Pittsburgh Sleep Quality Index (PSQI) as very poor sleepers (PSQI >10, n=80) and good sleepers (PSQI <6, n=19). They then underwent a polysomnography and in the morning rated their previous night’s sleep using a published protocol (Deutschen Gesellschaft für Schlafforschung und Schlafmedizin morning protocol [MP]).Results: In the polysomnography, significant differences were found between very poor and good sleepers according to the PSQI with respect to sleep efficiency and time awake after sleep onset. When comparing objective PSG and subjective MP, the polysomnographical sleep onset latency was significantly positively correlated with the corresponding parameters of the MP: the subjective sleep onset latency in minutes and the subjective evaluation of sleep onset latency (very short, short, normal, long, very long) were positively correlated with the sleep latency measured by polysomnography. The polysomnographical time awake after sleep onset (in minutes) was positively correlated with the subjective time awake after sleep onset (in minutes), evaluation of time awake after sleep onset (seldom, normal often), and subjective restfulness. The polysomnographical total sleep time (TST) was positively correlated with the subjective TST. Conversely, the polysomnographical TST was negatively correlated with the evaluation of TST (high polysomnographical TST was correlated with the subjective evaluation of having slept short or normal and vice versa). The polysomnographical sleep efficiency was positively correlated with subjective feeling of current well-being in the morning and subjective TST and negatively with subjective restfulness, subjective sleep onset latency, subjective evaluation of sleep onset latency, and evaluation of time awake after sleep onset.Conclusion: The data suggest that, in general, patients selected from the extremes of reported very poor sleepers and good sleepers have different amounts of sleep when measured in the laboratory, and that in general, the amount and timing of sleep in the laboratory are quite well perceived and reported by these groups. The data came from psychosomatic patients and suggest that even in this patient group, respective sleep complaints are more than just the expression of general somatization or lamenting. Keywords: Pittsburgh Sleep Quality Index, subjective sleep parameters, insomnia, awake after sleep onset, sleep disorders, sleep latency